2019
DOI: 10.1111/jfbc.12781
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and pro‐apoptotic activities of wild asparagus (Asparagus acutifoliusL.), black bryony (Tamus communisL.) and butcher's broom (Ruscus aculeatusL.) aqueous extracts against T24 and A549 cancer cell lines

Abstract: The aim of this study was to determine the phenolic profile, antiproliferative, and pro‐apoptotic activities of Asparagus acutifolius, Tamus communis, and Ruscus aculeatus aqueous extracts against human bladder (T24) and lung cancer (A549) cell lines. Antiproliferative activity of the extracts at the concentration range from 0.5 to 4 mg/ml was measured by MTT test, after the incubation period of 4, 24, 48, or 72 hr. Pro‐apoptotic activity of selected plant extracts against T24 and A549 cells was analyzed by fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The anticancer activity of polysaccharide, saponin, and flavonoid extracts from ASP has been reported in various cancers, such as lung and bladder cancer ( Bilušić et al, 2019 ), liver cancer ( Cheng et al, 2021 ), and ovarian cancer ( Xu et al, 2021 ). Some studies have found that asparagus saponin extracts have significant cytotoxic effects on colorectal cancer cells ( Jaramillo-Carmona et al, 2018 ), and the results of Bousserouel ( Bousserouel et al, 2013 ) and others have shown in more detail that methanolic extracts of ASP can induce apoptosis by activating the TRAIL death receptor pathway in SW480 and SW620 human colon adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer activity of polysaccharide, saponin, and flavonoid extracts from ASP has been reported in various cancers, such as lung and bladder cancer ( Bilušić et al, 2019 ), liver cancer ( Cheng et al, 2021 ), and ovarian cancer ( Xu et al, 2021 ). Some studies have found that asparagus saponin extracts have significant cytotoxic effects on colorectal cancer cells ( Jaramillo-Carmona et al, 2018 ), and the results of Bousserouel ( Bousserouel et al, 2013 ) and others have shown in more detail that methanolic extracts of ASP can induce apoptosis by activating the TRAIL death receptor pathway in SW480 and SW620 human colon adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…These beneficial activities have been associated with the presence of specific compounds in plants that are commonly used in this dietary pattern, including phenolic compounds, such as hydroxycinnamic and chlorogenic acid [181], saponins [182], flavones and flavonoids [99,101,183,184], tannins [126], polysaccharides [185], glucosinolates [186,187], and other organosulfur compounds [71,188]. The mechanisms involved in the bioactive properties of MD ingredients against cancer have not yet been thoroughly revealed, however, it is hypothesized that they modify the expression of hormones and growth factors that induce cancer pathogenesis [12].…”
Section: Cancermentioning
confidence: 99%
“…The consumption of the edible parts of wild asparagus could maximize the dietary intake of health beneficial compounds that have protective or disease preventive properties, because of their high content in polyphenols and the significant antioxidant and antiproliferative capabilities (Di Maro et al, 2013). Moreover, the extract of fresh young shoots of wild asparagus was found to have antiinflammatory and adaptogenic effects (Kasture et al, 2009), while the aqueous extract of Asparagus acutifolius had a high pro-apoptotic effect against cancer cell lines because of its various natural bioactive compounds (Bilusic et al, 2019). Fruit and leaves of wild asparagus could be considered as a source of natural agents (phenolic compounds, antioxidant, and cytotoxic activities) for the food and pharmaceutical industry (Kaska et al, 2018).…”
Section: Study Site and Plant Materialsmentioning
confidence: 99%